Pengaruh Permainan Bahasa Indonesia terhadap Kemampuan Berbicara pada Siswa PG -TK Plus Sutomo 1 Medan: The Influence of Indonesian Language Games on Speaking Skills of Students at PG-TK Plus Sutomo 1 Medan - Sherine Alexandra; Kristiawan Indriyanto; Dian Syahfitri (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This research examined the effect of using a language game approach on developing Indonesian speaking skills among students at PG-TK Plus Sutomo 1, Medan. This study was designed using an experimental method using a pretest-posttest format with a control group. The research data showed a significant improvement in students' speaking skills in the experimental group, with an average pretest score of 61.2, which increased to 77.5 after the posttest. The Paired Sample T-Test obtained a significance value of 0.001 (p < 0.05), while the Independent Sample T-Test obtained a significance value of 0.025 (p < 0.05). These results confirm that applying language game techniques significantly improves students' speaking skills. Although the effect size is relatively small (Cohen's d = 0.2), this finding indicates that the influence of language games on improving speaking skills is still limited in practice. However, applying this technique remains relevant because it fosters speaking courage, enriches vocabulary, and encourages active student involvement. It can also serve as a basis for further studies using a larger and more diverse sample range. This study concludes that the language game strategy is a practical approach to improving and developing students' Indonesian oral communication skills at PG-TK Plus Sutomo 1 Medan. Although the effects are relatively small in practical terms, this strategy is still beneficial in building speaking confidence, enriching vocabulary, and increasing active student participation. The implications of these findings suggest the need for further research with a larger sample size to more fully demonstrate the influence of language games on speaking skills.